(untitled) (Global Journal of Human-Social Science, 2018)
With consumption of about 3 of the world s total energy per annum India is the world s sixth largest energy consumer Exploring renewable energy sources has a strong worldwide interest in the meeting the energy needs of fast growing population both for environmental reasons release of pollutants and fossil reserves depletion and economical ones Most of the population in India does not have access to reliable energy India has millions of tonnes of unwanted available biomass often burnt inefficiently in open fields causing air pollution However this waste can be turned into a completely environment-friendly source of energy World economy is dominated by technologies that rely on fossil energy petroleum coal natural gas to produce fuels power chemicals and materials While the use of conventional energy like oil coal and electricity has increased enormously in the last 25 years in ASEAN economies India still imports crude oil petroleum over 111 92 million tonnes peryear This heavy dependence on imported oil leads to economic and social uncertainties Currently there is a strong worldwide interest in the development of technologies that allow the exploitation of renewable energy sources both for environmental release of pollutants and fossil reserves depletion and economical reasons